2019
DOI: 10.5539/gjhs.v11n8p51
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Stress in Families of Children With Autism Spectrum Disorder: The Roles of the Extended Family

Abstract: OBJECTIVE: This study focused on the role of extended family in mitigating the stress experienced by parents of children with autism and the possible challenges of involving them, especially in modern Nigerian society. The study identified the sources of stress for parents of children with autism, and considered location and family size factors in stress experienced by parents, the role of the extended family in mitigating the stress and the challenges that may inhibit the involvement of the extended family.&a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…The African parenting adage often goes "it takes a village to raise a child", and this proverb continues to hold wisdom in modern day parenting. Due to the intensive nature of parenting, which refers to the strenuous process of raising another human being into independence and adulthood [1], parents and caregivers tend to create networks with the extended family [2][3][4][5], educators [6], and healthcare professionals [7], among other individuals and communities to ensure their child's holistic development. The interaction between various stakeholders in child development is succinctly captured by Bronfenbrenner's ecological systems theory, which posits a nested structure of micro-and macro-systems in influencing child development [8].…”
Section: Introductionmentioning
confidence: 99%
“…The African parenting adage often goes "it takes a village to raise a child", and this proverb continues to hold wisdom in modern day parenting. Due to the intensive nature of parenting, which refers to the strenuous process of raising another human being into independence and adulthood [1], parents and caregivers tend to create networks with the extended family [2][3][4][5], educators [6], and healthcare professionals [7], among other individuals and communities to ensure their child's holistic development. The interaction between various stakeholders in child development is succinctly captured by Bronfenbrenner's ecological systems theory, which posits a nested structure of micro-and macro-systems in influencing child development [8].…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that parents as primary caregivers can be considered the initial experts on their children, spending more time with them than almost any other adult the child encounters in their day-to-day lifetime (Bordelon & Bradley, 2019). Although, it is important to note that parents of children with autism spectrum disorder symptoms themselves may need to interventions because of the high stress they experience (Anyanwu et al, 2019;Davis & Carter, 2008;Gong et al, 2015;McStay, Dissanayake, Scheeren, Koot, & Begeer, 2014;Pottie, Cohen, & Ingram, 2009;Soltanifar et al, 2015) and involving these parents in interventions for their children can reduce their stress and enhance their mental health (Catalano, Holloway, & Mpofu, 2018;Estes et al, 2014). As described earlier, previous studies have revealed that parent training is the most effective approach to the reduce children's screen-time and make communicative lifestyle (Adams et al, 2018;Özyurt et al, 2018;Sadeghi et al, 2019aSadeghi et al, , 2019bSadeghi et al, , 2019c, only a small proportion of families benefit from evidence-based interventions (Jensen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%